Effect of topical fluoride on microshear bond strength of primary enamel to composite, microhardness of enamel and its surface morphology: An in vitro study - Mina Biria; Sajedeh Namaei Ghasemi; Seyedeh Mahsa Sheikh-; Narges Panahandeh (Tabriz University of Medical Sciences, 2019)
Background. This in vitro study aimed to evaluate the microshear bond strength (μSBS), microhardness and morphological characteristics of primary enamel after treating with sodium fluoride (NaF) and acidulated phosphate fluoride (APF). Methods. Forty-eight primary canines were cut into mesial and distal sections and assigned to five groups randomly: group 1 (immersed in saliva as a control), group 2 (treated with NAF and immersed in saliva for 30 minutes), group 3 (treated with APF and immersed in saliva for 30 minutes), group 4 (treated with NAF and immersed in saliva for 10 days), and group 5 (treated with APF and immersed in saliva for 10 days). Composite resin (Filtek Z250) was bonded on the specimens (n=15) for measuring the μSBS. After storage in 37°C artificial saliva for 24 hours, µSBS and Vickers hardness tests (10 readings) were performed. The data were analyzed using one-way ANOVA and Kolmogorov-Smirnov, Levene's and Tukey HSD tests (P<0.05). Morphological analysis of enamel and modes of failure were carried out under a scanning electron microscope (SEM) on two remaining specimens. Results. Significant differences in μSBS were only noted between groups 2 and 4 (P=0.024). Group 3 showed a significant decrease in hardness after storage in artificial saliva (P<0.001), with a significantly lower hardness than the other groups (P<0.001). The SEM observations showed irregular particles in groups 3 and 5; uniform, smooth and thin coats were seen in groups 2 and 4. Conclusion. Fluoride therapy with NaF and APF gels prior to restorative treatments had no adverse effects on the microshear bond strength.